2017
DOI: 10.13005/ojc/330153
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Radical Scavenging Activity of Citrus Limon Peel Essential Oil

Abstract: The water distillated essential oil of Citruslimon collected from Ramsar, Province of Mazandaran, North of Iran collected in December 2013, was analyzed using gas chromatography (GC) and gas chromatography-mass spectroscopy (GC-MS). The yield of oil was 0.23% w/w. Twenty-one components representing 100% of the essential oil were characterized. Limonene (61.4%), b-pinene (13.1%) and g-terpinene (11.3%) were identified as the main constituents in the volatile oil. The antioxidant ability of the oil was examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 4 publications
1
8
1
Order By: Relevance
“…On the other hand, the yields in the present study for the mandarin/tangerine oils ( C. reticulate and C. reticulata × C. sinensis ) were higher than those reported for samples collected in Faisalabad, Pakistan, by Sadaf, Shahid, and Iqbal (), who attributed the lower yield (0.18 ± 0.03%) to the ripeness of the fruit. Gomes et al () reported higher yields that those found in the present study for C. aurantiifolia and C. limon grown in Lavras, Brazil, whereas Ghoorchibeigi, Larijani, Azar, Zare, and Mehregan, () and Tchameni, Mbiakeu, Sameza, Jazet, and Tchoumbougnang () reported lower yields than those found in the present investigation for samples of C. aurantiifolia and C. limon collected in Iran and Cameroon, respectively.…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…On the other hand, the yields in the present study for the mandarin/tangerine oils ( C. reticulate and C. reticulata × C. sinensis ) were higher than those reported for samples collected in Faisalabad, Pakistan, by Sadaf, Shahid, and Iqbal (), who attributed the lower yield (0.18 ± 0.03%) to the ripeness of the fruit. Gomes et al () reported higher yields that those found in the present study for C. aurantiifolia and C. limon grown in Lavras, Brazil, whereas Ghoorchibeigi, Larijani, Azar, Zare, and Mehregan, () and Tchameni, Mbiakeu, Sameza, Jazet, and Tchoumbougnang () reported lower yields than those found in the present investigation for samples of C. aurantiifolia and C. limon collected in Iran and Cameroon, respectively.…”
Section: Discussioncontrasting
confidence: 65%
“…The high quantity of monoterpenes followed by sesquiterpenes in the present study, with limonene as the major constituent of the C. reticulate, C. reticulata × C. sinensis , C. aurantiifolia and C. limon oils, is in agreement with data published on samples collected in other locations of Brazil for oranges (Badawy, Taktak, & El‐Aswad, ) and limes/lemons (Amorim et al, ; Gomes et al, ). The abundance of monoterpenes with limonene as the major component of Citrus oils has also been reported for samples from other countries, such as C. aurantiifolia in Vietnam (Dang et al, ), Cameroon (Tchameni et al, ), India (Fagodia, Singh, Batish, & Kohli, ) and Australia (Mirzaei‐Najafgholi, Tarighi, Golmohammadi, & Taheri, ); C. limon in India (Jain & Sharma, ) and Iran (Ghoorchibeigi et al, ); and C. reticulate in Vietnam (Dang et al, ), China (Tao, Jia, & Zhou, ), Pakistan (Zia et al, ), Nigeria (Ayoola et al, ) and Egypt (Hamdan, Mohamed, & El‐Shazly, ).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations